THE LIMITATION OF CYBER WARFARE UNDER HUMANITARIAN LAW (Pembatasan Perang Siber dalam Hukum Humaniter) - Amalia Zuhra; Laila Almira (Fakultas Hukum Universitas Trisakti, 2021)
States and non-State armed groups are increasingly employing cyber capabilities in their military operations in the digitalization environment today. There is a controversy about how current international legal frameworks, especially International Humanitarian Law (IHL), applies to such conduct in cyberspace, most notably in the context of armed conflict. Because one of the fundamental aims of the IHL is to protect civilians from the impact of armed conflict, it is critical to explore the norms of IHL that regulate such operations. This article will be likely to discuss about cyber warfare in the term of armed conflict. Lastly, the article will be reviewing the rules and principle that applies during the cyber warfare.